Could intra-tendinous hyperthermia during running explain chronic injury of the human Achilles tendon? - Farris, D. J.; Trewartha, G.; McGuigan, M. P. (Journal of Biomechanics, 2011)
Chronic tendinopathy of the human Achilles tendon (AT) is common but its injury mechanism is not fully understood. It has been hypothesised that heat energy losses from the AT during running could explain the degeneration of AT material seen with injury. A mathematical model of AT temperature distribution was used to predict what temperatures the core of the AT could reach during running. This model required input values for mechanical properties of the AT (stiffness, hysteresis, cross-sectional area (CSA), strain during running) which were determined using a combination of ultrasound imaging, kinematic and kinetic data. AT length data were obtained during hopping and treadmill running (12 kmph) using ultrasound images of the medial gastrocnemius (50 Hz) and kinematic data (200 Hz). AT force data were calculated from inverse dynamics during hopping and combined with AT length data to compute AT stiffness and hysteresis. AT strain was computed from AT length data during treadmill running. AT CSA was measured on transverse ultrasound scans of the AT. Mean±sd tendon properties were: stiffness=176±41 N mm-1, hysteresis=17±12%, strain during running=3.5±1.8% and CSA=42±8 mm2. These values were input into the model of AT core temperature and this was predicted to reach at least 41 °C during running. Such temperatures were deemed to be conservative estimates but still sufficient for tendon hyperthermia to be a potential cause of tendon injury.